International standards for identifying public health emergencies - Faisal Abdullah , Israa; Abbas Khudair , Assist.Prof.whaj (Basra studies journal, 2022)
Health security is one of the components of the global system that is safeguarded by specialized international organizations that work on setting a set of standards. Ensuring health security is not considered an exclusive competence of the health sector, but rather a group of sectors and actors intervene to achieve it. In addition to the health authorities, a group of other Sultans play very important roles in order to implement, monitor and enforce respect for health directives and instructions issued by the World Health Organization. While, the World Organization has set the necessary criteria for imposing emergency situations, as health risks, especially in the event of epidemics, become risks that cross the continents of the world and do not recognize the geographical borders between countries, and the evidence for this is the rapid and unexpected transmission of the epidemic. As it spreads in a short time and the infection is transmitted to most countries of the world, and in view of the effects of health security on the economy and development, the developed countries make the health security of citizens one of the most important pillars of their comprehensive security.